Immunologic barriers in liver transplantation: a single-cell analysis of the role of mesenchymal stem cells - Li, Haitao; Yu, Saihua; Liu, Haiyan; Chen, Lihong; Liu, Hongzhi; Liu, Xingwen; Shen, Conglong (Frontiers in Immunology, 2023)
Background: This study aimed to analyze the biomarkers that may reliably indicate rejection or tolerance and the mechanism that underlie the induction and maintenance of liver transplantation (LT) tolerance related to immunosuppressant or mesenchymal stem cells (MSCs). Methods: LT models of Lewis-Lewis and F344-Lewis rats were established. Lewis-Lewis rats model served as a control (Syn). F344-Lewis rats were treated with immunosuppressant alone (Allo+IS) or in combination with MSCs (Allo+IS+MSCs). Intrahepatic cell composition particularly immune cells was compared between the groups by single-cell sequencing. Analysis of subclusters, KEGG pathway analysis, and pseudotime trajectory analysis were performed to explore the potential immunoregulatory mechanisms of immunosuppressant alone or combined with MSCs. Results: Immunosuppressants alone or combined with MSCs increases the liver tolerance, to a certain extent. Single-cell sequencing identified intrahepatic cell composition signature, including cell subpopulations of B cells, cholangiocytes, endothelial cells, erythrocytes, hepatic stellate cells, hepatocytes, mononuclear phagocytes, neutrophils, T cells, and plasmacytoid dendritic cells. Immunosuppressant particularly its combination with MSCs altered the landscape of intrahepatic cells in transplanted livers, as well as gene expression patterns in immune cells. MSCs may be included in the differentiation of T cells, classical monocytes, and non-classical monocytes. Conclusions: These findings provided novel insights for better understanding the heterogeneity and biological functions of intrahepatic immune cells after LT treated by IS alone or in combination with MSCs. The identified markers of immune cells may serve as the immunotherapeutic targets for MSC treatment of liver transplant rejection.